CHAIRMAN OF COUNCIL’S ADDRESS - Kanya, Prof. James Ireri (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Good morning and a warm welcome to the MUSTIC2024 Conference. It is my privilege to address you as the Head of the Council of Meru University of Science and Technology. Our theme, "Science in the Service of Climate Action," underscores the critical role that scientific inquiry and innovation play in addressing one of the most urgent challenges of our time. At Meru University, we are dedicated to being a beacon of academic excellence, providing transformative education that empowers students to make a global impact. This conference aligns perfectly with our goals, integrating scientific research and education into practical solutions for climate resilience. Climate change impacts every aspect of our lives, and this conference brings together experts from diverse fields to explore comprehensive solutions. Our sub-themes reflect this interdisciplinary approach, mirroring our strategic initiatives aimed at fostering a holistic response to climate challenges. We strive to be a catalyst for ground-breaking research and innovation. In Agriculture and Food Sciences, we focus on sustainable agroecological practices essential for food security and climate resilience. Our strategic plan supports research in climate-smart agriculture, equipping our community with tools to combat climate-related challenges. Business and Economics explore sustainable entrepreneurship and carbon credit markets to drive climate-positive business strategies. This shift prioritizes environmental stewardship alongside economic growth, preparing students to lead in a green economy. As a bridge between academia and industry, we leverage computing and informatics technologies to adapt to and mitigate climate impacts. Our strategic plan includes cutting-edge programs in computing, ensuring our graduates lead in technological solutions for climate resilience. To nurture an environment where every student thrives, we emphasize education’s role in climate change mitigation. Training individuals with necessary skills and understanding social sciences influences behavioural changes, developing leaders equipped to tackle climate issues. Our strategic initiatives integrate climate education across all disciplines, fostering environmentally conscious leaders. Engineering and Architecture offer sustainable solutions for infrastructure and urban environments. Our strategic plan encourages research in eco-friendly building technologies. Health Sciences, including Nursing, examine the link between climate change and public health. Addressing the health impacts of environmental changes requires a proactive approach. Nurses, at the forefront of healthcare delivery, advocate for sustainable practices and address health issues related to environmental changes. Meru University invests in health sciences research and nursing programs that incorporate climate health, preparing students to meet these challenges. In Pure and Applied Sciences, we explore climate change prediction and nature-based innovations for effective resource management and conservation. Our strategic focus supports research in these areas, ensuring that our scientific community contributes to sustainable practices. This conference is a platform for sharing knowledge, fostering collaboration, and driving innovation. As we engage in these discussions, let us be inspired by the expertise gathered here and work towards practical solutions. Meru University’s strategic plan aligns with these goals, and we are committed to leading the way in climate resilience through education and research.